Implementasi Nilai-Nilai Kepahlawanan TGKH. Muhammad Zainuddin Abdul Madjid dalam Pembentukan Karakter Siswa di SMP Negeri 1 Sikur Lombok Timur - Badarudin Badarudin; Khairi Ahmad Shopian; Habibuddin Habibuddin (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
This study aims to describe the forms and values of the heroism of TGKH. Muhammad Zainuddin Abdul Madjid in shaping the character of the students of 1st State High School, Sikur East Lombok. This type of research is descriptive qualitative research with a phenomenological approach. The results of the study explained that the values of heroism that students possess are martial spirit, passion for learning, a social attitude, and also cultural values. This spirit becomes a value in the formation of the character of the student and becomes the primary basis for the development of character.